DEVELOPMENT OF A BIOLOGY MODULE INTEGRATING IMTAQ VALUES WITH A PROBLEM BASED LEARNING APPROACH TO ENVIRONMENTAL POLLUTION MATERIALS - Fatemah Rosma; Mauizah Hasanah; Vivi Yunisa Harahap (Jurnal Biologi Sains dan Kependidikan, 2024)
It is appropriate to instill IMTAQ values in science, especially biology, so that students not only understand scientific facts, but also the divine meanings in them. This research aims to determine the feasibility of a biology module integrating IMTAQ values with a problem based learning approach to the environmental pollution sub-material. This module development research refers to the EDDIE development model (Analysis, Design, Development, Development or Production, Implementation or Delivery and Evaluations). The subjects of this research were 30 students of the Biology Education Study Program, Muhammadiyah University of Aceh. The data collection instrument used an IMTAQ-based biology learning module feasibility questionnaire. From the research results, the percentage of module validation by material experts was 78,13% (quite valid). Meanwhile, the percentage of material validation in the area of integration of IMTAQ values was 83.5% (very valid)., and the percentage of modules by media experts was 77,17% (quite valid). The student assessment of the module obtained a percentage of 81,40% which means that the module is suitable for use as teaching material. The average N-Gain score was 0,86  which means in the high category.